2008
DOI: 10.1080/03640210801929287
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Model of Early Argument Structure Acquisition

Abstract: How children go about learning the general regularities that govern language, as well as keeping track of the exceptions to them, remains one of the challenging open questions in the cognitive science of language. Computational modeling is an important methodology in research aimed at addressing this issue. We must determine appropriate learning mechanisms that can grasp generalizations from examples of specific usages, and that exhibit patterns of behavior over the course of learning similar to those in child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
1
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 41 publications
2
85
1
1
Order By: Relevance
“…In contrast to existing models of verb class acquisition (Alishahi & Stevenson, 2008;Niyogi, 2002;Perfors, Tenenbaum & Wonnacott, 2010) which assumed that children use adult-like semantics and syntactic features to acquire verb classes, the present work suggested that children can assign some verbs to classes based on word co-occurrence information. However, because language acquisition in the present model included a message with various kinds of meaning, it is important to characterise how our account differs from these accounts.…”
Section: Grammaticality Ratingscontrasting
confidence: 98%
See 2 more Smart Citations
“…In contrast to existing models of verb class acquisition (Alishahi & Stevenson, 2008;Niyogi, 2002;Perfors, Tenenbaum & Wonnacott, 2010) which assumed that children use adult-like semantics and syntactic features to acquire verb classes, the present work suggested that children can assign some verbs to classes based on word co-occurrence information. However, because language acquisition in the present model included a message with various kinds of meaning, it is important to characterise how our account differs from these accounts.…”
Section: Grammaticality Ratingscontrasting
confidence: 98%
“…Various mechanistic accounts of how verb classes might be learned from semantic and syntactic information have been proposed (Alishahi & Stevenson, 2008;Niyogi, 2002;Perfors, Tenenbaum & Wonnacott, 2010). Learning in these models was quick, because their cues for verb bias were adult-like and optimal for solving this problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from initially small and concrete representations, it learns incrementally long representations (syntagmatic growth) as well as more abstract ones (paradigmatic growth). Several models address either paradigmatic (Alishahi and Stevenson, 2008;Chang, 2008;Bannard et al, 2009) or syntagmatic (Freudenthal et al, 2010) growth. This model aims to explain both, thereby contributing to the understanding of how different learning mechanisms interact.…”
Section: Introductionmentioning
confidence: 99%
“…those of lower complexity, as already solved by the learner. For instance, models addressing the acquisition of grammatical constructions and their meaning (Kwiatkowski et al, 2012;Alishahi and Stevenson, 2008;Gaspers and Cimiano, in press;Chang and Maia, 2001) typically learn from symbolic input. In particular, assuming that the child is already able to segment a speech signal into a stream of words and to extract structured representations from the visual context, such models typically explore learning from sequences of words and symbolic descriptions of the non-linguistic context.…”
Section: Introductionmentioning
confidence: 99%